The The silence of the letters: Slavery, education and freedom in Rio de Janeiro (Brazil, 19th century) - Lima Da Silva, Alexandra (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2021)
Objective: The goal of this paper is deciphering the “silence of letters” and to understand the meanings of enslaved and freed people’s education and instruction in Imperial Rio de Janeiro. Originality/contribution: The article suggests reading and learning about other historical experiences with the intent of questioning the widespread understanding that African enslaved people weren’t educated. Method: Based on a comparative method and analysis of sources, the article seeks to understanding the existence of subjects made invisible in academic production: literate and educated enslaved women and men. Through the movement of connections, it is essential to map out the debate around the instruction and education of enslaved people in academic studies of the African diaspora in the Americas. Strategies/information collection: Does studying other African diaspora experiences help understanding Brazil? Conclusions: The article conclusion is that the meaning of education and literacy for enslaved people in the Americas allows for a more complex understanding of the Brazilian case, with particular attention given to the city of Rio de Janeiro in the 19th Century.